'A Joke less Killing'. animated remediation of a comic book as an extra-mediation. Issue 3 (3rd May 2020) - Żaglewski, Tomasz
ABSTRACT: The aim of this article is to present a specific type of comics' based animated features – namely DC Universe Animated Original Movies – throughout the re-interpretation of Drew Morton's remediation approach. By using titles as 'The Killing Joke' – both as a graphic novel and its animated re-creation – author is trying to 'expand' the remediation's original concept by Jay David Bolter and Richard Grusin (followed by Morton's application of it for the comic-based film materials) by proposing an 'intra-mediation'/'extra-mediation' categories. As a result it becomes possible to re-consider DC Universe full-length animations (as a challenges for the original comics' content) that are significally limiting/broadening the re-mediated attributes of initial graphic narratives.